Leitura de poemas contribuições para a compreensão leitora de alunos do 5º ano de uma escola pública de João Pessoa - Ferreira, Anunciada Maria Vieira (2025)
Over time, we have observed some progress in reading instruction. However, many challenges still need to be overcome. Data from the 2022 PISA (Program for International Student Assessment) reveals that Brazil scored 410 points in low reading performance. This figure is higher than the rates of countries like Chile, Uruguay, and Argentina. Echoes of this gap are heard in a 5th-grade class at Dom Adauto Municipal School, located in João Pessoa, where we teach. We encounter students who display significant reading difficulties, from the most elementary level (decoding) to identifying symbolic elements that shape their critical thinking. Given this issue, this work promotes a participatory and civic-minded practice designed to encourage young readers. The research methodology is anchored in a qualitative approach, based on action research. Thus, our proposal was based on planning, organizing, and implementing a variety of activities that directly address the real needs still present in everyday school life. From a theoretical perspective, this research is supported by the assumptions of Solé (1998), Soares (2023), Kleiman (2002), Orlandi (1999, 2002, 2007, 2014, 2023), and Pêcheux (2014), and in conjunction with official documents such as the BNCC (National Common Curricular Base, 2017). For data collection and intervention, this research was developed from July to November 2024, with classes taught with active and integrated activities through the discursive genre—poem. For that, we worked on the theme—Identity—as a way of valuing cultural traits and strengthening pluralistic and democratic teaching. The research involved 33 (thirty-three) students who interacted in class, producing texts and revealing their subjectivities. As a research tool, we developed a Pedagogical Guidance Notebook as a way to share our work and socialize with the school community, as well as the academic community.